A Narrative Review on the Anti-inflammatory Potential of Mamsyadi Yoga: Bridging Ayurveda and Modern Pharmacology - Rani, Poonam; Gusain, Tanvi (International Research Journal of Ayurveda & Yoga, 2025)
Background: There is a scarcity of Agada Yogas in the market which requires scientific exploration. Aims and Objectives: The aim and objective of the study are to understand Shotha and inflammation and to study the probable efficacy of Mamsyadi Yoga in Shotha condition. Materials and Methods: The pharmacodynamic properties of plants were taken from Ayurveda Pharmacopoeia of India and anti-inflammatory studies were taken from the past 10 years through Google Scholar and PubMed. Discussion: The Mamsyadi Yoga is composed of 10 ingredients and each ingredients possess anti-inflammatory properties individually. As per Ayurveda also, the formulation was found to be dominant in Tikta Rasa, Laghu Guna, Ushna Veerya, and Katu Vipaka. Inflammation is the most common biological response when the body is exposed to microorganisms or toxic compound, or unwanted responses and is ultimately involved in the pathology of diseases initially. Conclusion: Mamsyadi Yoga can be a useful Agada used in treating anti-inflammatory activities and implicating the principles of Agada in modern-day Visha.